2000
DOI: 10.1128/jcm.38.6.2156-2161.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Filamentous Phage Associated with Recent Pandemic Vibrio parahaemolyticus O3:K6 Strains

Abstract: A specific serotype, O3:K6, of Vibrio parahaemolyticus has recently been causing epidemics of gastroenteritis in Southeast Asia, Japan, and North America. To examine whether the new O3:K6 strains possess characteristics that may exacerbate outbreaks, we compared V. parahaemolyticus O3:K6 strains with non-O3:K6 strains using strains isolated from individuals with traveler's diarrhea at Kansai Airport Quarantine Station, Osaka, Japan. All 24 O3:K6 strains possessed a common plasmid, pO3K6 (DNA size, 8,782 bp, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Previous studies demonstrated a strong association of filamentous phages, f237, with recent pandemic strains of V. parahaemolyticus. This phage possesses a unique ORF8 open reading frame that is found only in recent pandemic isolates, and the Zot (Zonula occludens toxin)-like toxin previously described in the V. cholerae is reported to be encoded in the ORF7 [51,52]. A match was found between the CRISPR spacer region of V. anguillarum PF7 with a zot-encoding prophage in V. anguillarum PF4, indicating the contribution of CRISPR to the phage resistance of this bacterium [53].…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies demonstrated a strong association of filamentous phages, f237, with recent pandemic strains of V. parahaemolyticus. This phage possesses a unique ORF8 open reading frame that is found only in recent pandemic isolates, and the Zot (Zonula occludens toxin)-like toxin previously described in the V. cholerae is reported to be encoded in the ORF7 [51,52]. A match was found between the CRISPR spacer region of V. anguillarum PF7 with a zot-encoding prophage in V. anguillarum PF4, indicating the contribution of CRISPR to the phage resistance of this bacterium [53].…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies predicted the zot-like genes to reside on prophage elements in three V. anguillarum strains isolated from Chile, the UK and the US, respectively [26], and suggested that the loss of a zot-encoding prophage reduced virulence against fish larvae in a pathogenic V. anguillarum [27]. These results suggest that Inovirus-related prophages may spread in V. anguillarum and that inoviruses could contribute to the virulence of this bacterium, as proposed for the related species V. cholerae and V. parahaemolyticus [13,14,23,28].…”
Section: Introductionmentioning
confidence: 68%
“…Sequencing of the putative replicative forms revealed two novel Inovirus genomes, pVAI1 and pVAI2. The genomes of pVAIs consisted of 6117 bp, were predicted to encode 11 ORFs, had a GC content of 42.5% and contained two intergenic regions corresponding to conserved sequences of inoviruses [13,28]. Global alignment of the genomes of pVAI1 and pVAI2 exhibited a pairwise identity of 99.95%.…”
Section: Characterization and Annotation Of Pvais In Vibrio Anguillarummentioning
confidence: 99%
“…ORFs from f237 were found among the identified prophage sequences. The phage f237 has been linked to pandemic clones since 1996, and is thought to play a key role in increasing bacterial virulence [ 53 ]. Furthermore, VP32 had prophage sequences from the Myoviridae family, while the HP1 and SHP/2 genomes contained prophage sequences from the Myoviridae and Siphoviridae families.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, VP32 had prophage sequences from the Myoviridae family, while the HP1 and SHP/2 genomes contained prophage sequences from the Myoviridae and Siphoviridae families. These phages are members of the order Caudovirales, which includes marine bacteriophages known to infect Vibrio sp [ 53 , 54 ]. Apart from being acquired horizontally, some of these prophages could have integrated into the sequenced bacterial genome and may have been transferred vertically through generations [ 55 ].…”
Section: Resultsmentioning
confidence: 99%